This is the Way the World Ends: A Philosophy of Civilization Since 1900, and A Philosophy of the Future - Hanna, Robert; Paans, Otto (Cosmos and History: The Journal of Natural and Social Philosophy, 2021)
The aim of this essay is to provide, in an accessible, concise, and synoptic format, a new Kulturphilosophie, or "philosophy of civilization,” that covers the period running from the turn of the 20th century to the end of the second decade of the 21st century. Our use of the term Kultur ("culture” or "civilization”) is intended not only to emphasize that we are philosophizing about civilization as a whole since 1900”including philosophy itself, the applied and fine arts, the formal and natural sciences, society, and politics. It is also intended to emphasize that we view civilization in this maximally broad sense, during this 120-year period, as a product of certain philosophical, artistic, scientific, social, and political conditions that have also generated a certain world-image or "world-picture” (Weltbild) that has more or less non-self-consciously characterized humanity's development and guided its course during that period”but towards what? Answer: towards our collective rational human condition right now and right here, namely, Spring 2020 in the midst of the COVID-19 pandemic, at The End of the World. More precisely, we are claiming that the past 120 years of civilization have effectively driven humanity into a veritable cul de sac, a dead end for rational human civilization. As a consequence, we most urgently need to retrace our steps, identify a philosophico-cultural version of Robert Frost's "road not taken” that briefly appeared between 1900 and 1940, and then correspondingly revolutionize our thinking towards a philosophy of the future that can and should extend beyond The End of the World and into the next four decades of the 21st century. We call this philosophy of the future new wave organicism. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]>